Reduction of oil uptake in vacuum fried Pleurotus eryngii chips via ultrasound assisted pretreatment - Ren, Aiqing; Cao, Zhenzhen; Tang, Xiaoxian; Duan, Zhenhua; Duan, Xu; Meng, Xiangyong (Frontiers in Nutrition, 2022)
The reduction of oil uptake in vacuum-fried Pleurotus eryngii chips by ultrasound assisted pretreatment was investigated regarding the pore structure changes. Pore structure of P. eryngii chips with four pretreatments, such as blanching, blanching + osmosis, blanching + ultrasound and blanching + ultrasound assisted osmosis was determined by mercury intrusion porosimetry (MIP) and scanning electron microscopy (SEM). In addition, the quality parameters of vacuum-fried P. eryngii chips such as hardness, rehydration ratio, reducing sugar, protein and oil content were also measured. The results showed that the oil absorption of vacuum fried P. eryngii chips was affected by the porous structure. The oil content of vacuum fried P. eryngii chips was significantly and positively correlated with the pores with diameters above 50, 5–50, and 0.5–5 μm in the samples both before and after vacuum frying, while negatively correlated with the pores with diameters below 0.5 μm. Ultrasound pretreatment changed the microporous structure of P. eryngii chips, effectively hindering the oil absorption of samples. In particular, ultrasound assisted osmosis pretreatment induced the formation of more micropores. It was concluded that blanching + ultrasound assisted osmosis pretreatment is a promising method to reduce oil absorption and improve the quality of vacuum fried foods.